Feeding ecology of silky sharks Carcharhinus falciformis associated with floating objects in the western Indian Ocean. Issue 4 (14th December 2016) - Filmalter, J. D.; Cowley, P. D.; Potier, M.; Ménard, F.; Smale, M. J.; Cherel, Y.; Dagorn, L.
Abstract : The silky shark Carcharhinus falciformis is commonly associated with floating objects, including fish aggregating devices (FADs), in the Indian Ocean. While the motives for this associative behaviour are unclear, it does make them vulnerable to capture in the tuna purse seine fishery that makes extensive use of FADs. Here, the diet of 323 C. falciformis, caught at FADs in the Indian Ocean, was investigated to test the hypothesis that trophic benefits explain the associative behaviour. A high proportion of stomachs with fresh contents (57%) suggested that extensive feeding activity occurred while associated with FADs. Multiple dietary indices showed that typical non‐associative prey types dominated, but were supplemented with fishes typically found at FADs. While the trophic benefits of FAD association may be substantial, our results suggest that associative behaviour is not driven solely by feeding.